Microsoft Exchange 2013 Cookbook - Horenbeeck, Michael Van; Tender, Peter De (Packt Publishing, Limited, 2013)
This book is a practical, hands-on guide that provides the reader with a number of clear, step-by-step exercises."Microsoft Exchange 2013 Cookbook" is targeted at network administrators who deal with the Exchange server in their day-to-day jobs. It assumes you have some practical experience with previous versions of Exchange (although this is not a requirement), without being a subject matter expert.